Calcium-Binding Protein S100P Promotes Tumor Progression but Enhances Chemosensitivity in Breast Cancer - Cong, Yizi; Cui, Yuxin; Wang, Suxia; Jiang, Lei; Cao, Jianqiao; Zhu, Shiguang; Birkin, Emily; Lane, Jane; Ruge, Fiona; Jiang, Wen G.; Qiao, Guangdong (Frontiers in Oncology, 2020)
Background: Chemoresistance remains one of the obstacles to overcome in the treatment of breast cancer. S100 calcium-binding protein P (S100P) has been observed to be overexpressed in several cancers and has been associated with drug resistance, metastasis, and prognosis. However, the role of S100P in chemoresistance in breast cancer has not been thoroughly determined. Methods: Immunohistochemistry was used to evaluate the expression level of S100P protein in 22 pairs (pre-chemo and post-chemo) of breast cancer tissue from patients who underwent neoadjuvant chemotherapy. The influence of S100P on the biological behavior and chemosensitivity of breast cancer cells was then investigated. Results: The protein level of S100P in breast cancer tissue was significantly higher than in benign fibroadenoma (p<0.001). The S100P expression level was shown to be decreased by 46.55% after neoadjuvant chemotherapy (p=0.015). Subgroup analysis revealed that S100P reduction (57.58%) was mainly observed in the HER2+ tumors (p=0.027). Our in-vitro experiments showed that the knockdown of S100P suppressed the proliferation, adhesion, migration and invasion abilities of T47D and SK-BR-3 breast cancer cells. We further demonstrated that this knockdown increased the chemoresistance to paclitaxel and cisplatin in SK-BR-3 cells. We found that S100P exerted its function by activating NF-κB, CCND1 and Vimentin, but downregulating E-cadherin. Conclusions: S100P promotes the aggressive properties of breast cancer cells and may be considered as a promising therapeutic target. Moreover, S100P can be used to predict the therapeutic effect of chemotherapy in HER2+ breast cancer patients.